2014
DOI: 10.2214/ajr.13.12013
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Contrast Injection Protocol to Tube Potential for Cardiovascular CT

Abstract: Lower tube potential (100 kV) for cardiothoracic CT could be accompanied by a 44% reduction in contrast volume with satisfactory aortic blood-pool attenuation in most patients. More personalized adaptation of the contrast protocol that takes into account patient characteristics and tube potential is necessary to ensure sufficient contrast enhancement for all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…For the CT scanner investigated in this study, the maximum tube current was 740 mA at 100 and 120 kVp, while the maximum tube current was 635 mA at 140 kVp. Additionally, prior studies have shown that the iodine contrast attenuation is lower in CCTA images acquired with a higher kilovoltage peak [ 20 , 21 , 22 ], so the 140 kVp scan is usually not used in our clinical routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…For the CT scanner investigated in this study, the maximum tube current was 740 mA at 100 and 120 kVp, while the maximum tube current was 635 mA at 140 kVp. Additionally, prior studies have shown that the iodine contrast attenuation is lower in CCTA images acquired with a higher kilovoltage peak [ 20 , 21 , 22 ], so the 140 kVp scan is usually not used in our clinical routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplying Q-ICE at 85.5 kg for cohort 2 by 0.82 (52.3 HU × 0.82 = 42.9 HU) agrees well with cohort 3's Q-ICE at 85.5-kg value of 42 HU. This finding has motivated our CT protocol optimization team to consider lowering volumes for 120 kV or raising volumes for 140 kV 23 …”
Section: Discussionmentioning
confidence: 99%
“…This finding has motivated our CT protocol optimization team to consider lowering volumes for 120 kV or raising volumes for 140 kV. 23 To our knowledge, Q-ICE is the first institution-wide, automatable metric for contrast enhancement quantification. The work of Johnson et al 24 is the closest study to our work.…”
Section: Discussionmentioning
confidence: 99%